On the “Fluidity” of a Middle Byzantine Building Crew (on the Example of the Imperial Churches of the 1040s) - Vinogradov, Andrey Yu. (Actual Problems of Theory and History of Art, 2019)
The paper deals with the comparison of building techniques on the churches of the Byzantine emperors and the Kiev Prince in the 1040s and the reconstruction of the chronology of the building crews working for them. Before 1042–1043, on the order of dioiketes John Organotrophos, the Lycian masters rebuilt St. Nicholas in Myra, inaugurated later, under Constantine IX Monomachos. The latter attached these builders to the Constantinopolitan masters for the reconstruction of the Anastasis church in Jerusalem, executed between 1042–1043 and 1047. Constantine sent a similar group of masters no later than 1044 to the island of Chios, where they joined “Helladic” builders working here previously for execution of the katholikon of Nea Mone, finished before 1049; the Anatolian masters could come to Jerusalem and to the Chios independently, or from one site to another. Finally, Constantinopolitan and “Helladic” masters from this crew were given by the same Emperor to Yaroslav of Kiev, probably after the conclusion of the Byzantine-Russian peace in 1046. The chronology of these crews can be reconstructed approximately as follows: 1041–1043 —Myra, 1043–1046 — Jerusalem, 1044–1048 — Nea Mone, from 1047 — Chernigov.
Keywords: Middle Byzantine architecture; Old Russian architecture; building techniques; architectural decoration; 11th century; Constantine Monomachos; Myra; Jerusalem; Chios; Chernigov; Constantinople